Insect pollination services in actively and spontaneously restored quarries converge differently to natural reference ecosystem. (15th September 2022) - Carvalho, Carolina; Oliveira, Amália; Caeiro, Elsa; Miralto, Otília; Parrinha, Marta; Sampaio, Ana; Silva, Carmo; Mira, António; Salgueiro, Pedro A.
Abstract: Ecological restoration has the potential to accelerate the recovery of biodiversity and ecosystem services in degraded ecosystems. However, current research queries whether active restoration is necessary. We evaluated plant-pollinator networks during spring at replicated sites within an actively restored quarry, at abandoned quarries undergoing spontaneous restoration, and within a natural reference area, to compare pollinator community composition and function. Overall, we aimed to assess which approach is more effective in rehabilitating pollination networks. We found that while both approaches allowed for the restoration of pollination function, active restoration provided faster recovery: pollination network structure was more similar to the reference ecosystem after 20–30 years of active restoration, than 40 years of natural succession in spontaneously restored areas. Different restoration approaches sustained distinct pollinator communities providing a similar service in different areas: honey bees played an important role in the natural area, bumblebees in the abandoned quarries and wild bees in the restored sites, suggesting a possible conflict between diverse wild bee communities and honey bee homogenized pollinator communities. In quarries, flower resource availability and diversity influenced networks' structural properties by constraining species interactions and composition. In spontaneously restored areas a rich herbaceous layer of ruderal species from early successional stages buffered against the shortage of flower resources at critical periods. Active restoration, though effective, should include practices that consider wild bee communities and mitigate flower resource scarcity. The use of "bridging" plants that flower in different periods, should be considered in active restoration programs to enhance the pollinator community. Graphical abstract: Image 1 Highlights: Restoration strategy effectiveness is compared using interaction networks. Assisted and spontaneous approaches restore pollination, but assisted does so faster. Distinct restoration approaches generated key structural vegetation differences. Structural vegetation differences sustained distinct pollinator communities. Distinct pollinator communities provide a similar service in different areas.